Casualty Per Cent dalam Perhitungan Etat Hutan Tanaman Jati Perum Perhutani (Casualty Per Cent on AAC Determination of Teak Forest Plantation in Perum Perhutani) - Rohman (Institut Pertanian Bogor (IPB University), 2008)
The research was aimed to detect the change of forest area over planning periods to estimate casualty over production period of forest management. It is undeniable fact that teak plantation area has inevitable risk due to bad practices of illegal logging, deforestation, and forest degradation. However, Perum Perhutani does not consider these risk factors in the company yield regulation and annual allowable cut (AAC) determination. The results show that the percentage of forest area that changed into the higher age class by order from the lowest age class were 16.3% (age class I to II), 33.74% (age class II to III), 3.36% (age class III to IV), 31.54% (age class IV to V), 19.69% (age class V to VI), and 15.73 % (age class VI to VII). The casualty per cent calculated from age class I, II, III, IV, V, VI were 75%, 70%, 55%, 54%, 32%, and 16%, respectively. The AAC regarding to the casualty per cent for planning period 2005-2014 in Bagian Hutan Kradenan Utara was 595 m3/year, while the current AAC calculation was 1.840 m3/th, regardless the casualty percent.